EVALUATION OF PLEURAL FLUID C-REACTIVE PROTEIN IN ETIOLOGICAL DIAGNOSIS OF PLEURAL EFFUSION - Barabde, Wrishikesh M. (Journal of Biomedical and Pharmaceutical Research, 2020)
Background: Pleural effusions are a common adverse effect of fluid buildup inside the pleural area.due to the anatomical nature and lack of a direct access, this condition is a top diagnostic challenge. The treatment varies depending on the pleural illness. One of two things the pleural effusion can do is either particular or general qualities. When there may be an imbalance between pleural fluid creation and absorption, pleural effusion occurs. Currently, the distinction between exudative and transudative effusion is made using Light’s criteria. If the pleural effusion is exudative, a thorough diagnostic workup is required to identify the likely local cause of the fluid. Exudative pleural effusions are currently assessed in addition with pleural fluid mobileular mobility and differentials, glucose level, adenosine deaminase (ADA), fluid GeneXpert for Mycobacterium TB (MTb), fluid culture, and cytology. The sensitivity and specificity of the aforementioned checks, however, are unreliable. Because CRP in the pleural fluid might result from increased diffusion from the blood due to infected capillary leaking, the levels of pleural fluid CRP are likely to reflect serum CRP levels. Aim: Evaluation of pleural fluid c-reactive protein in etiological diagnosis of pleural effusion Material and Method: This was a possible observational study that was conducted. Fifty patients with pleural effusion in all were selected for the research, and the amount of CRP in the pleural fluid was measured. All of the subjects had interviews with element records, exams, and investigations in accordance with the predesigned and pretested proforma. Patients’ informed permission was obtained before they could take part in the trial. CRP-Turbilatex-Quantitative Turbidimetric Immunoassay, which is based entirely on the classical agglutination response, was used to measure the CRP in pleural fluid. Results: Our investigation found significant differences in serum, fluid levels, and fluid/serum ratios for LDH, total protein, and CRP in addition to CRP fluid/serum ratio for each organisation. A strong association between CRP, LDH, and total protein fluid levels developed. One incidence of liver cirrhosis and one case of cardiac effusion were found among the 50 patients with pleural effusion. The pleural fluid test was performed after the diuretics were stopped in the three instances since they had been getting them and had become, by Light’s standards, transudative. Conclusion: The estimation of pleural fluid In order to differentiate between exudative and transudative effusions, CRP might be utilised as a diagnostic tool. Moreover, pleural fluid CRP is a statistically significant marker for separating exudative effusions that are not tubercular from tubercular effusions. CRP levels in pleural fluid can be utilised as an additional diagnostic tool for exudative effusions. It makes a clear distinction between parapneumonic effusions and empyema and tuberculous and malignant effusions. Keywords: CRP, LDH, Transudative effusions, Exudative effusions, liver cirrhosis, Tuberculous, Pleural fluid, MTb, ADA.